2006
DOI: 10.1002/cne.21054
|View full text |Cite
|
Sign up to set email alerts
|

Particular subpopulations of midbrain and hypothalamic dopamine neurons express vesicular glutamate transporter 2 in the rat brain

Abstract: Vesicular glutamate transporters (VGLUT1, ‐2, and ‐3) mediate the accumulation of transmitter glutamate into synaptic vesicles in glutamatergic neurons. VGLUT1 and VGLUT2 are more reliable glutamatergic neuron markers, since VGLUT3 also exists in other neuron types. To study whether the dopaminergic neuron uses glutamate as a cotransmitter, we analyzed VGLUTs expression in dopamine neurons of adult male rats by in situ hybridization and immunohistochemistry. In the ventral midbrain, in situ hybridization analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
220
1
5

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(258 citation statements)
references
References 73 publications
27
220
1
5
Order By: Relevance
“…In line with previous reports (Dal Bo et al, 2004;Hur and Zaborszky, 2005;Kawano et al, 2006;Yamaguchi et al, 2007), using single-cell RT-PCR we detected a subpopulation of purely glutamatergic (i.e., not expressing TH) neurons in the VTA/SN region. We detected them in freshly dissociated neurons at P0 as well as in acute VTA/SN horizontal brain slices prepared from P14 TH-GFP and VGluT2-EGFP mice (supplemental Fig.…”
Section: Existence Of a Subpopulation Of Glutamatergic Neurons In Thesupporting
confidence: 92%
See 2 more Smart Citations
“…In line with previous reports (Dal Bo et al, 2004;Hur and Zaborszky, 2005;Kawano et al, 2006;Yamaguchi et al, 2007), using single-cell RT-PCR we detected a subpopulation of purely glutamatergic (i.e., not expressing TH) neurons in the VTA/SN region. We detected them in freshly dissociated neurons at P0 as well as in acute VTA/SN horizontal brain slices prepared from P14 TH-GFP and VGluT2-EGFP mice (supplemental Fig.…”
Section: Existence Of a Subpopulation Of Glutamatergic Neurons In Thesupporting
confidence: 92%
“…However, the expression of VGluTs in DA neurons in vivo has remained controversial. Whereas initial in situ hybridization studies failed to detect VGluT transcripts in the ventral mesencephalon (Fremeau et al, 2001;Gras et al, 2002;Schafer et al, 2002;Herzog et al, 2004) (but see Fremeau et al, 2002), a recent in situ hybridization study, Kawano et al (2006) showed that VGluT2 mRNA is found in a small subset of DA neurons of the medial nuclei of the A10 cell group in adult rats. Another similar study reported only very few DA neurons coexpressing VGluT2 in the adult VTA (Yamaguchi et al, 2007).…”
Section: Glutamate As a Cotransmitter In Da Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past few years, with the identification of the vesicular glutamate transporters (3)(4)(5)28), it has been possible to analyze the vesicular glutamate packaging properties of the mDA neurons. Several groups, including ours, have shown that a subset of mDA neurons expresses Vglut2 mRNA, a finding that makes the use of glutamate as a neurotransmitter a possibility in these neurons (14,29,30). Kawano et al (29) showed that the area containing the most Vglut2-and TH-expressing neurons was the RLi, with somewhat lower expression in the interfascicular nucleus, the rostral part of the caudal linear nucleus, the parabrachial pigmented nucleus, and the paranigral nucleus of the VTA.…”
Section: Discussionmentioning
confidence: 87%
“…Studies examining the expression of Vglut2 in midbrain DA neurons have shown this cophenotype to be present in both the SNc and VTA from early development to adult stages (Dal Bo et al, 2004;Mendez et al, 2008;Birgner et al, 2010). However, it has been emphasized that the cophenotype is more abundant in VTA than SNc neurons, at least in the postnatal rat (Dal Bo et al, 2004Kawano et al, 2006;Mendez et al, 2008;Yamaguchi et al, 2011). Moreover, whereas VGLUT2 protein has been detected in DA axon terminals (tyrosine hydroxylase-positive) of both the NAc and DStr in the preadolescent rat, it could no longer be observed in the adult (Bérubé-Carrière et al, 2009;Moss et al, 2011).…”
Section: Sensitized Phenotype Caused By Neuroadaptations Increases Rementioning
confidence: 99%